Transmastoid Labyrinthectomy for Menière's Disease: Experience and Outcomes. Issue 10 (December 2020) - Bergmark, Regan W.; Semco, Robert S.; Abdul-Aziz, Dunia; Rauch, Steven D.
Abstract : Objective: To characterize presurgical symptoms and treatment history and postoperative course in patients with medically recalcitrant Menière's disease undergoing transmastoid labyrinthectomy in the post-intratympanic gentamicin era. Study Design: Retrospective case series. Setting: Tertiary academic medical center. Patients: All patients who underwent transmastoid labyrinthectomy for medically recalcitrant Menière's disease in 2003 to 2019 by the senior author. Interventions: Review of patients' medical records for: preoperative history of drop attacks, gentamicin injections, endolymphatic sac decompression or vestibular neurectomy, preoperative audiograms, length of hospital stay, postoperative complications, and persistent symptoms or challenging recovery. Main Outcome Measures: Presurgical clinical history and proximal postoperative outcomes. Results: Seventy-two patients with a mean age of 56.7 (standard deviation [SD] 10.7) were included. All cases were unilateral. Forty-three patients (59.7%) suffered from drop attacks. Sixty-two (86.1%) had failed sufficient symptom control with gentamicin injections. The mean preoperative word recognition score was 36.4% (SD 23.7) versus 95.1% (SD 8.5) in the contralateral ear. The mean pure-tone average (PTA) of the ipsilateral ear before surgery was 65.5 dB (SD 18.0) versus 16.2 (SD 13.5) for the contralateral ear. Mean hospital stay was 2.0 days (SD 0.87 days, range of 1–5 d). Three patients (4.2%) had prolonged postoperative vertigo. Conclusions: Transmastoid labyrinthectomy at our center is performed for unilateral Menière's disease, generally when intratympanic gentamicin has failed. A majority of surgical patients suffer from drop attacks preoperatively. Hospital stay is typically brief.